A high-performance TRIP steel enhanced by ultrafine grains and hardening precipitates. (5th August 2017) - Xie, P.; Han, M.; Wu, C.L.; Yin, Y.Q.; Zhu, K.; Shen, R.H.; Chen, J.H.
Abstract: Using thermo-mechanical processing, a heterogeneous microstructure with ultrafine grains and efficient hardening nanoprecipitates was introduced into a transformation induced plasticity (TRIP) steel with composition of Fe-12Mn-2Ni-Mo-Ti-(Al), such that the fabricated steel has an excellent combination of yield strength, ductility and thermal stability. It is shown that the Laves phase precipitates which hindered the ultrafine grains from coarsening were formed at high temperature, whereas the most efficient hardening nanoprecipitates inside these ultrafine grains were introduced at a lower temperature. The former precipitates are hexagonal (Fe, Mn)2 (Mo, Ti) Laves phase containing Si and the later nanoprecipitates belong to the B2 phase. Graphical abstract: Highlights: A heterogeneous microstructure with ultrafine grains and nanoprecipitates was fabricated by thermomechanical processing. The ultrafine-grained steel has an excellent combination of yield strength, ductility and thermal stability. The composition and structure of Laves phases, as well as its effects on ultrafine grained steel, were studied.